Modern Concurrency Abstractions for C# - Benton, Nick; Cardelli, Luca; Fournet, Cédric (ACM Transactions on Programming Languages and Systems (TOPLAS), 2002)
Polyphonic C# is an extension of the C# language with new asynchronous concurrency constructs, based on the join calculus. We describe the design and implementation of the language and give examples of its use in addressing a range of concurrent programming problems.
Superseded by ECOOP version.